A preliminary investigation into the restorative potential of public aquaria exhibits: a UK student-based study. (2nd January 2017) - Cracknell, Deborah; White, Mathew P.; Pahl, Sabine; Depledge, Michael H.
Abstract: Even 'managed' natural settings, such as botanical gardens and zoos, can provide restorative experiences. Well-being benefits may also be greater in land/waterscapes with greater biodiversity (eg, species richness). Using two photo studies with student participants, we explored aesthetic and behavioural preferences, affect and the restorative potential of multiple public aquaria exhibits, including variation in biodiversity. Study 1 ( N  = 39) found that aquarium exhibits, in general, scored as highly as natural environments (eg, green space) on all dimensions. Study 2 ( N  = 40) examined whether responses were influenced by exhibit characteristics including: climatic region (tropical/temperate), biological group (vertebrates/invertebrates), species richness (high/low) and abundance of individuals (high/low). Supporting predictions, tropical, vertebrate (fish) and high species richness exhibits were generally rated more positively than temperate/invertebrate/low species richness exhibits. However, some low richness/high abundance exhibits were also rated unexpectedly positively. Findings are discussed within the context of the growing well-being and biodiversity literature.